Epidemiological characterization of incident cases of Rickettsia infection in rural areas of Urabá region, Colombia (2018)
ABSTRACT: Introduction, Most of the studies related to rickettsial infection in Colombia are cross-sectional because of the challenge in conducting prospective studies on infectious disease that may have a difficult diagnosis. Although cross-sectional studies are essential to detect people exposed to rickettsiae, they are not suited to demonstrate the recent circulation of this pathogen in areas at risk of transmission. Objective To characterize the epidemiology of incident cases of Spotted fever group (SFG) rickettsial infection in humans and equines from rural areas of Uraba ́ region in Colombia where out- breaks of rickettsiae previously occurred. Materials and methods A prospective study was conducted in the Alto de Mulatos and Las Changas in the Uraba ́ region. Serum samples and socio-ecological information were collected from 597 people enrolled in 2015, and a second sample was collected from 273 people a year later. Indirect immune-fluorescence assays for detection of IgG antibody against rickettsiae were done using slides with Rickettsia rickettsii antigens. A titer ≥128 was considered positive. Incident cases were defined as (i) serological conversion of IgG titers from seronegative to seropositive or (ii) at least a four-fold increase in IgG end point titers in the second sample. Results The cumulative incidence of rickettsial infection was 6.23% (95%CI 3.67–9.78) in humans and 32.31% (21/65) of incident cases in equines. Incident cases were mostly females